Cytoxic, Anti-Microbial and Antioxidant activity-guide fraction from Garcinia Nervosa / Khong Heng Yen - Yen, Khong Heng; Nur Ulfa, Nurr Maria; Mian, Vivien Jong Yi (2014)
There are several local Malaysian Garcinia species which have ethnobotanical uses but so far little studies have been carried out to link these folkloric uses with the phytochemistry of these plant species. It would be interesting therefore, to develop a phytochemical data of one such Sarawakian species which is Garcinia nervosa, a species not reported before.Some species of Garcinia have been shown to possess interesting biological activities such as cytotoxic, antibacterial, antioxidant and anti-cancer activities. Leaves and stem bark samples of Garcinia nervosa will be extracted and purified using standard protocols which involves the conventional extraction technique such as chromatographic methods. Analyses for structural elucidations of pure bioactive compounds will involve the usual spectroscopic techniques such as NMR, FTIR, UV and MS. The isolation and identifications of these natural products will lead us to establish a profile of chemical and biological activities of the extract for standardization and product development. The outcome of this project is a document of medicinal plants rich in active compounds for further investigation for potential in drug development